Nursing leadership in intensive care units and its relationship to the work environment - Alexandre Pazetto Balsanelli; Isabel Cristina Kowal Olm Cunha (Universidade de São Paulo, 2015)
AIM: To establish whether there is any relationship between the work environment and nursing leadership at intensive care units (ICUs).METHOD: Correlational study conducted at four ICUs in southern São Paulo (SP), Brazil. The study population was comprised of 66 pairs (nurses and nursing technicians) established by lottery. The nurses responded to three instruments: 1) characterization; 2) a validated Portuguese version of the Nursing Work Index Revised (B-NWI-R); and 3) Grid & Leadership in Nursing: ideal behavior. The nursing technicians responded to 1) characterization and to 2) Grid and Leadership in Nursing: actual behavior, relative to the corresponding randomly-assigned nurse. The data were analyzed by means of analysis of variance (ANOVA) at p ≤ 0.05.RESULTS: The work environment was not associated with actual nursing leadership (p = 0.852). The public or private nature of the institutions where the investigated ICUs were located had no significant effect on leadership (p = 0.437). Only the nurse-physician relationship domain stood out (p = 0.001).CONCLUSION: The choice of leadership styles by nurses should match the ICU characteristics. Leadership skills could be developed, and the work environment did not exert any influence on the investigated population.